Investigation of the mycelial compatibility of Macrophomina phaseolina in the Carpatian Basin - Csüllög, Kitti; Prokopics, Stella; Tarcali, Gábor (Acta Agraria Debreceniensis, 2022)
Macrophomina phaseolina is a globally widespread fungal pathogen. The fungus has a very wide range of hosts. Under optimal conditions, M. phaseolina can cause serious damage tothe host plants. In this study, the mycelial compatibility of different M. phaseolina isolates was investigated. From 2019 to 2021, 12 sunflower samples were collected from different regions of the Carpathian Basin, 9 samples from Hungary, 1 sample from Austria, and 2 samples from Slovakia. The genetic variability of the pathogen is a critical problem in plant protection. Two compatible pathogen strains can easily exchange their genetic material for each other, which can lead to the development of resistance. All collected samples (12) were tested to examine their compatibility. Isolates from all tested samples were paired with isolates from all other samples thus, a total of 66 pairings were made. During the examinations of mycelial compatibility, only 20 pairs of all possible pairings were found to be incompatible, and all others (46) were found to be compatible.